EMPOWERING STREET CHILDREN IN NIGERIA: NON-FORMAL EDUCATION AND COUNSELLING POTENTIALS - Yusuf, Murtala Akanbi; TSAGEM, SHEHU YAHAYA (Sokoto Educational Review, 2022)
The phenomenon of street children has been described as one of the serious growing social problems in Nigeria. The phenomenon of street children has come to stay as a permanent feature of societies across the globe. This implies that whatever effort is made to salvage the situation should emphasize taking the immediate needs of these children to them on the streets rather than eradicating street children. This is the reason why this paper advocate for the empowerment of street children through the instrumentality of non-formal education and counselling. The paper argued that living alone, lack of education, poor nutrition, diseases, homelessness, poverty, destitution, exploitation, and substance abuse among others are common features of street children. The paper concludes that street children can be empowered through the exploration of potentials of non-formal education and counselling such as basic literacy, post-literacy, vocational skills, health and nutritional education, destitution education, rehabilitation, and abode education